Pengaruh Debt to Equity Ratio, Firm Size dan Net Profit Margin Terhadap Kinerja Keuangan Perusahaan Pada Perusahaan Sub Sektor Perbankan Yang Terdapat Pada Bursa Efek Indonesia Periode Tahun 2020 - 2022 - Fatah Nur Abdul Aziz; Diana Puspitasari; Suhita Whini Setyahuni; Amalia Nur Chasanah (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
Financial performance analysis is analysis that used to measure company achievement from financial segment. this study purposes is to asses the impact of financial ratio, firm size and net profit margin to financial performance in banking sub-sector companies listed on Indonesia Stock Exchange Period 2020 - 2022. This research utilizes secondary data obtained from a sample of 45 companies. The analytical methodology employed in this study is descriptive analysis, normality test, hetroscedasticity, autocorelation, multicollinearity, multiple linear regression, coefficient of determination and F test from SPSS statistics 25 as the analytical instrument. The result found in this study show that Net Profit Margin variable has an influence on Return on Assets, meanwhile the Debt to Equity Ratio dan Firm Size variable does not exert influence Return on Assets